Análisis de la justicia restaurativa para atender casos de violencia intrafamiliar en el Centro de Atención Integral a Víctimas de Violencia Intrafamiliar (CAVIF) de la Fiscalía General de la Nación, Colombia (2010)
The actual investigation makes an emphasis about restorative justice, its oriented to catch the attention for those cases of inner familiar violence, cases that are being taking care of the integral centre attention for victims of domestic violence (CAVIF). Existence of the following analysis appears on the basis of conceptual work and methodological exercise, all applied from a process of collecting, systematizing and analyzing information based on a design of exploratory investigation. Study had an intentional sample, 20 female users and 18 professionals from (CAVIF) proceeded with a series of profound interviews designed based on categories previously defined. This way it's described all kind of context needs, institutional, professional and own users and functionaries of the system in order to comprehend the necessary conditions, proposing general alignments for the formulation of a restorative justice on accordance of actual by law in Colombia. Results of the study are permitting point to the necessity of carry on different process of capacitating the restorative justice functionaries, responsible for allowing the necessary steps to the domestic violence conflicts in the (CAVIF). As a last it is a criteria proposed in order to carry on a justice restorative program.